Laser therapy in 100 tracheobronchial tumours. Issue 5 (May 1985) - Hetzel, M R; Nixon, C; Edmondstone, W M; Mitchell, D M; Millard, F J; Nanson, E M; Woodcock, A A; Bridges, C E; Humberstone, A M
Abstract : One hundred patients with tracheobronchial tumours were treated with the neodymium YAG (yttrium-aluminium-garnet) or argon laser for symptoms of airways obstruction caused by tumour (59 cases), complete collapse of a lung (17 cases), or recurrent haemoptysis (24 cases). Seventy four of them had relapsed or failed to respond to radiotherapy or chemotherapy and all were inoperable. Objective improvement in results of lung function tests or haemoptysis diary charts was seen in 37 patients with airways obstruction (63%), five (29%) with collapsed lung, and 14 (58%) with haemoptysis. Overall, 68 patients had symptomatic benefit and there was objective improvement in 56. Two deaths occurred in 288 treatment sessions both occurring as a result of asphyxia from minor haemorrhage in patients with advanced cylindromas and critical narrowing of the trachea or single remaining bronchus. In suitable patients with intraluminal tumour laser phototherapy is a valuable addition to conventional treatment.